The smooth life: Instagram as a platform of control. Issue 1 (1st April 2020) - Fisher, Tabitha
In this article, I will focus primarily on how Instagram has been used as a means of public control by rewarding the continuous projection of a relentlessly positive self-image. Furthermore, the article will discuss the performative nature of the Instagram platform and how it facilitates the subjugation of women by creating a flirty-and-fun frictionless space that turns their bodies, thoughts and feelings into commodities. Left unchecked, smooth platforms like Instagram provide a distraction that delays society's dealings with the present. To conclude this article will present a selection of Instagram artists whose projects encourage us to think critically about the smooth as a demonstration of how women might combat this force of nature.